Nutrition effects of the supermarket revolution on urban consumers and smallholder farmers in Kenya - Matin Qaim; Camilla I. M. Andersson; Christine G. K. Chege; Simon C. Kimenju; Stephan Klasen; Ramona Rischke (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
Food systems in developing countries are transforming, involving a rapid expansion of supermarkets. This supermarket revolution may affect dietary patterns and nutrition, but empirical evidence is scarce. The few existing studies have analyzed implications for food consumers and producers separately. We discuss a more integrated framework that helps to gain a broader understanding. Reviewing recent evidence from Kenya, we show that buying food in supermarkets instead of traditional outlets contributes to overnutrition among adults, while reducing undernutrition among children. For farm households, supplying supermarkets causes improvements in dietary quality. The results underline that supermarkets influence nutrition in multiple ways and directions.
Keywords: D12; I15; O12; O15; Q12; 330; supermarkets; obesity; malnutrition; nutrition impacts; developing countries; Kenya